Hormonal contraceptive use, menstrual dysfunctions, and self-reported side effects in elite athletes in Denmark - Oxfeldt, M.; Dalgaard, B. L.; Jørgensen, A. A.; Hansen, M. (International Journal of Sports Physiology and Performance, 2020)
Objective: To identify the prevalence of hormonal contraceptive (HC) use, menstrual cycle disturbances, and self-perceived physical and emotional symptoms related to the menstrual cycle/pill cycle in elite female athletes. Methods: One hundred eighty-six Danish elite female athletes completed an online questionnaire to assess menstrual status and history, use of HCs, and self-perceived physical and emotional symptoms related to the menstrual cycle or HC use. Results: Fifty-seven percent of elite female athletes in Denmark use HC, with 74% using combined HCs and 26% using progestin only. Sixty percent of oral contraceptive users reported having manipulated their menstrual cycle by continuous oral contraceptive use. Forty-nine percent of non-HC users had a regular menstrual cycle, while 51% experienced menstrual disturbances, with 1 athlete being primary amenorrheic and 13 athletes having secondary amenorrhea. Menstrual disturbances were experienced by a larger proportion of endurance athletes (69%) compared with athletes performing power and technical disciplines. In endurance athletes amenorrhea was associated with a higher cardiovascular training volume (P < .001). Negative symptoms related to the menstrual/pill cycle were reported by both HC and non-HC users, whereas positive physical symptoms were experienced more often among the non-HC (14%) versus HC users (2%) (P < .01). Notably, 13% of the athletes reported that negative symptoms sometimes/always caused them to not participate in or complete the scheduled training. Conclusion: HC use is common among elite athletes, and continuation of HC is used to manipulate the menstrual cycle in relation to sport competitions. HC use does not abolish dysmenorrhea, but it may reduce emotional-related side effects. Menstrual disturbances are frequent in endurance athletes and are associated with cardiovascular training volume.